Explaining regional variations in mother-child health: Additional identified determinants in India and Bangladesh - Susmita Dasgupta; Subhendu Roy; David Wheeler (Elsevier, 2021)
This paper explores the sources of spatial variation in child wasting and maternal anemia in three Indian states and six Bangladeshi divisions.  Our initial probability models incorporate traditionally-cited variables from Demographic and Health Surveys such as mother's education, mother's age and household wealth, along with seasonal fluctuations and regional fixed effects. The regional fixed effects are highly significant, even after controlling for the traditionally-cited determinants.  We then re-estimate our models, replacing regional fixed effects with measures of four factors that exhibit spatial clustering in the study area: provision of health services, political instability, religious culture, and flood-proneness.  Our re-estimated models show highly significant effects for all four factors, thereby highlighting potential gains from more effective policy interventions at the regional level.  Mothers and children whose socioeconomic status is identical have much better health outcomes in areas where health services are relatively plentiful, political stability prevails, key protein sources are more plentiful, and water is abundant.  Our results also demonstrate a strong association of mother's health status post-partum with long term health outcomes for children.